Upgrading of wood waste bio-oil via transesterification - Noraziani, Binti Lot (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Depletion of fossil fuels leads to a research to find an alternative source to replace it. Esterification and transesterification are the most widely used upgrading method to produce biofuels with similar properties as petroleum fuels. This study attempted to improve the bio-oil properties produced from microwave pyrolysis by using heterogeneous transesterification reaction with calcium oxide (CaO) as catalyst. The objectives of this study are to improve the pyrolytic bio-oils properties and to determine the ideal weight ratio of methanol/bio-oil for transesterification reaction. Dried sample of wood waste is subjected to microwave pyrolysis to produce pyrolytic bio-oil. The bio-oil is then upgraded using transesterification reaction with the aid of CaO and carried out in two different weight ratio of methanol/bio-oil. Characterization of the bio-oil before and after transesterification reaction shows that the properties of bio-oil are successfully improved. Gross calorific values of upgraded bio-oil are 32.949 and 34. 483 MJ/kg. Based on the experimentations, ideal weight ratio of methanol/biooil is 2:1 which greatly improved certain bio-oil properties. In conclusion, although this weight ratio improves certain properties of bio-oil the most important properties of bio-oil which is calorific value are reduced significantly.